Kontroversi Pinjaman Online Ditinjau Dari Perspektif Moral - Ratna Kartikawati; Soediro Soediro (Kosmik Hukum, 2022)
This research is motivated by the rise of online loan cases, online easy credit loans are currently being favored by the public because the process is easy and very helpful when there is an urgent need, while funds do not yet exist. at the bank. On the other hand, this online loan does not guarantee the confidentiality of customer data and does not protect customers from illegal debt collection practices. The purpose of this study was to obtain findings about the Online Loan Controversy from a Moral Perspective. The research will be conducted with a qualitative approach. The subjects in this study were credit customers in Purwokerto. Subjects were determined based on purposive sampling based on the characteristics of borrowing customers. The data collection method used: (1) in-depth interviews, (2) Focus Group Discussions/FGDs, conducted to collect information about the Online Loan Controversy Viewed from a Moral Perspective, its advantages and disadvantages, as well as important opinions and useful input in evaluating the Online Loan Controversy. Moral Perspective. Data analysis in this study uses an interactive model from Miles and Hubermans through the stages of data reduction, data presentation and verification. Based on the results of research and discussion, it can be seen that the selection of loans in borrowing by consumers is based on the compulsion and urgent need of consumers to fulfill their daily needs. These actions are actions that are not based on moral considerations, consumers do not consider on the basis of right and wrong, inappropriate and unfair. can provide loan installments, the consequences that arise are 2 (two), namely; The customer will be given the option to make a loan again with a nominal above the loan and must close the previous loan accompanied by a guarantee that will be agreed upon. Second, the loan will take valuables if the customer is unable to pay the agreed loan installments or if the agreement has stated the object of the guarantee, the guarantee belongs to the loan completelyKeywords: Juridical, Moral Judgment, Online Loas